The Quantum Fluctuations in the Dark Energy: An Introductory Study - Dr. Kapil Deo Singh (International Journal of Control and Automation, 2020)
The evidence for dark energy or some other effect that is currently accelerating the expansion of the universe is compelling. Though, it was first shown through high red shift Type 1 A supernovae (Bisogni et al. 421), there is now other evidence from other types of studies primarily associated with the cosmic microwave radiation that provide fairly strong supporting evidence. We think something is weird is going on with the universe, may be dark energy, may be some other effect we are not sure. Dark energy is shaking the foundations of theoretical physics. Some people think that the nature of the dark energy is the number one unsolved problem in theoretical physics. And this paper will deal with the possible physical mechanisms explaining the dark energy, what it is physically at the microscopic level.